Across‐vendor standardization of semi‐LASER for single‐voxel MRS at 3T. (18th December 2019) - Deelchand, Dinesh K.; Berrington, Adam; Noeske, Ralph; Joers, James M.; Arani, Arvin; Gillen, Joseph; Schär, Michael; Nielsen, Jon‐Fredrik; Peltier, Scott; Seraji‐Bozorgzad, Navid; Landheer, Karl; Juchem, Christoph; et al.
Abstract: The semi‐adiabatic localization by adiabatic selective refocusing (sLASER) sequence provides single‐shot full intensity signal with clean localization and minimal chemical shift displacement error and was recommended by the international MRS Consensus Group as the preferred localization sequence at high‐ and ultra‐high fields. Across‐vendor standardization of the sLASER sequence at 3 tesla has been challenging due to the B1 requirements of the adiabatic inversion pulses and maximum B1 limitations on some platforms. The aims of this study were to design a short‐echo sLASER sequence that can be executed within a B1 limit of 15 μT by taking advantage of gradient‐modulated RF pulses, to implement it on three major platforms and to evaluate the between‐vendor reproducibility of its perfomance with phantoms and in vivo. In addition, voxel‐based first and second order B0 shimming and voxel‐based B1 adjustments of RF pulses were implemented on all platforms. Amongst the gradient‐modulated pulses considered (GOIA, FOCI and BASSI), GOIA‐WURST was identified as the optimal refocusing pulse that provides good voxel selection within a maximum B1 of 15 μT based on localization efficiency, contamination error and ripple artifacts of the inversion profile. An sLASER sequence (30 ms echo time) that incorporates VAPOR water suppression and 3D outer volume suppression was implemented with identical parameters (RF pulse type and duration, spoiler gradients and inter‐pulse delays) on GE, Philips and Siemens and generated identical spectra on the GE 'Braino' phantom between vendors. High‐quality spectra were consistently obtained in multiple regions (cerebellar white matter, hippocampus, pons, posterior cingulate cortex and putamen) in the human brain across vendors (5 subjects scanned per vendor per region; mean signal‐to‐noise ratio > 33; mean water linewidth between 6.5 Hz to 11.4 Hz). The harmonized sLASER protocol is expected to produce high reproducibility of MRS across sites thereby allowing large multi‐site studies with clinical cohorts. Abstract : Harmonization of the single‐voxel sLASER sequence on three major MR vendors (GE, Philips and Siemens) has resulted in high quality and reproducible spectra in multiple brain regions (cerebellar white matter, hippocampus, posterior cingulate cortex, pons and putamen) at 3 T.